Bone Loss in Ankylosing Spondylitis: Does Syndesmophyte Formation Have an Influence on Bone Density Changes? - Kaya, Arzu; Ozgocmen, Salih; Kamanli, Ayhan; Ardicoglu, Ozge (Karger, 2009)
Objective: The aim of this study was to assess bone mineral density (BMD) using dual-energy X-ray absorptiometry (DXA) in a group of patients with ankylosing spondylitis (AS) and the factors which have an impact on bone mass. Also, a subgroup of patients not treated with anti-osteoporotic or disease-modifying anti-rheumatic drugs was followed for 24 months to assess potential influencing factors on BMD changes. Subjects and Methods: Fifty-five patients (42 males, 13 females) with AS were enrolled in the study. Clinical examinations were performed. BMD was measured using DXA at lumbar spine (L2-L4) and proximal femur (femur neck BMD and total femur BMD). Lumbar spine radiographs were scored using the Stoke Ankylosing Spondylitis Spine Score (SASSS). Twenty-one of 55 patients who completed 24 months of follow-up without using the aforementioned medications were reassessed. Results: Active patients (Bath Ankylosing Spondylitis Disease Activity Index >4, n = 22) had significantly lower femur neck and total BMD compared to inactive patients (n = 33), whereas spinal BMD was not different. Follow-up data revealed a 3.4% increase in spinal BMD but 0.9% and 0.25% decreases in femur neck BMD and total femur BMD, respectively. Percent changes in BMD measurements and SASSS scores were not significantly different between active (n = 10) and inactive (n = 11) patients. Conclusion: Significant increase in spinal BMD in parallel with increased SASSS revealed that spinal involvement prominent with new bone formation, sclerosis and syndesmophytes may influence spinal BMD measurements using DXA methods in AS. Proximal femur measurements seem to be less affected from disease-related new bone formation. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Ankylosing spondylitis; Bone mineral density; Syndesmophyte